Politics of inclusion : castes, minorities, and affirmative action - Hasan, Zoya, 1947- (New Delhi : Oxford University Press, 2009)
Analyses the policies and debates surrounding the lower castes and minorities disadvantaged and exclusion in India.
Includes bibliographical references (p. [272]-288) and index.
Keywords: Dalits -- Political aspects -- India; Dalits -- Government policy -- India; Minorities -- Political aspects -- India; Minorities -- Government policy -- India; Reverse discrimination in employment -- India; India -- Scheduled tribes -- Political activity; India -- Scheduled tribes -- Government policy